3D printing of multifunctional hydrogel scaffolds based on recombinant collagen for bile duct repair - Jianquan Zhang; Yuanhui Gao; Yijun Yang; Qiuhua Cheng; Longbao Feng; Zhongwen Lei; Xiaoyu Zhang; Yang Xiang (APL Materials)
Bile duct injuries remain a significant clinical challenge following hepatobiliary surgeries. Recently, 3D-printed tubular scaffolds have shown promise as effective solutions for bile duct tissue repair. This study presents a novel bi-layered bile duct scaffold, fabricated using advanced three-dimensional printing technology. The inner layer of this scaffold is constructed from poly(ε-caprolactone) methacrylate (PCLMA), which imparts high mechanical strength. The outer layer is composed of biocompatible methacrylated recombinant type I collagen (rColMA) and ε-poly(L-lysine)-methacrylamide (EPLMA), providing excellent antibacterial properties. In addition, encapsulated interleukin-6-loaded liposomes (IL-6@Lip) are incorporated into the outer layer to further promote tissue regeneration. This innovative design creates an optimal microenvironment for the growth and differentiation of bone marrow mesenchymal stem cells (BMSCs) into bile duct-like cells. These differentiated cells contribute to bile duct tissue regeneration, as evidenced by the expression of key differentiation markers, including CK7, CK19, AQP1, AE2, and CX43. The rColMA/EPLMA/IL-6@Lip hydrogel in the outer layer of the scaffold significantly enhances BMSC proliferation and their differentiation into bile duct epithelial cells. Furthermore, in vivo experiments show that the PCLMA//rColMA/EPLMA/IL-6@Lip bi-layered scaffold does not induce bile stasis. This novel, pre-differentiated 3D-printed active scaffold offers valuable insights into bile duct tissue regeneration and replacement research.